2020
DOI: 10.1111/joor.12915
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between displacement of the masseter muscle during biting and masseter muscle quality and bite force in healthy elderly persons

Abstract: Background Although age‐related changes in muscle quality influence muscle strength, the relationship between masseter muscle (MM) quality and maximum biting force (MBF) has never been studied. Objective The aims of the study were to verify the relationship among MM quality, MBF, and the displacement of the MM while biting forcefully (MMD) and to clarify the age‐related decline in MBF in healthy elderly persons. Methods Seventy‐four healthy community‐dwelling individuals (mean age, >65 years) from Tokyo metrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…After discussion, an agreement was reached, or a consensus was established with the third author. After the full-text reading and analysis of the 136 full texts, 49 studies were included in the final analysis [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…After discussion, an agreement was reached, or a consensus was established with the third author. After the full-text reading and analysis of the 136 full texts, 49 studies were included in the final analysis [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hara et al 20 found a tongue strength and chewing force diminish with age. Hara et al 21 found a reduction in the quality of masseter muscle contractions during mastication with the increase in age. These findings are due to the changes in the tonus and mobility of stomatognathic structures inherent to the ageing process, which are the main causes of presbyphagia.…”
Section: Discussionmentioning
confidence: 99%
“…In adults less than 65 years of age, the presence of anterior tooth prostheses is more likely to be associated with severe dental caries and poor oral hygiene [41,42]; therefore, they have a higher probability of having periodontal disease due to insufficient plaque control. The results in adults aged above 65 years show that the loss of facial muscle function with increasing age is likely to cause food accumulation on the buccal aspect [43,44], thereby making the management of the molar prostheses difficult. In addition, the frequency of use of oral care products tends to decrease with age, accelerating periodontal disease and leading to poor oral hygiene, and factors such as systemic diseases may contribute to fewer visits to the dentist and, thus, affect the occurrence of periodontal disease.…”
Section: Discussionmentioning
confidence: 99%